2011
DOI: 10.2298/jsc100921124l
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the mechanism of the formation of a bisheterocyclic compound containing Si and Ge by reaction of germylene silylene (H2Ge=Si:) and ethene

Abstract: The mechanism of the cycloaddition reaction between singlet state germylene silylene (H2Ge=Si:) and ethene was investigated by the CCSD(T)//MP2/6-31

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, few studies have been done on the addition reactions of germylenoid. Only the addition reactions of some germylenoid with ethylene [13][14][15][16][26][27][28][29][30][31] and formaldehyde [32] have been reported in the literature. Recently, we have calculated the addition reaction of H2GeLiCl with acetone and found that the product is a heterocyclic germanium compound, which provides new inspiration for the synthesis of new germanium-containing compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have been done on the addition reactions of germylenoid. Only the addition reactions of some germylenoid with ethylene [13][14][15][16][26][27][28][29][30][31] and formaldehyde [32] have been reported in the literature. Recently, we have calculated the addition reaction of H2GeLiCl with acetone and found that the product is a heterocyclic germanium compound, which provides new inspiration for the synthesis of new germanium-containing compounds.…”
Section: Introductionmentioning
confidence: 99%